Utilization of AI in Optimizing the Legislative Oversight Function Innovation to Increase Government Transparency and Accountability in the Digital Era - Fernando, Agung; Fakrulloh, Zudan Arief (International Journal of Social Service and Research, 2025)
The digital era presents both challenges and opportunities for the oversight function of the Indonesian House of Representatives (DPR RI). The complexity of government and increasing data volumes demand innovation in oversight mechanisms. This qualitative research, based on secondary data analysis from academic journals, government reports, international organization publications, and other relevant sources, explores the potential for utilizing Artificial Intelligence (AI) to optimize the legislative oversight function and improve the transparency and accountability of the Indonesian government. The results of the analysis show that AI can be applied in various areas of oversight, such as budget analysis, monitoring the implementation of laws and policies, and managing public aspirations, through technologies such as Natural Language Processing and Machine Learning. The use of AI has the potential to strengthen the DPR's analytical capacity, encourage evidence-based accountability, and improve access to information. However, its implementation faces significant challenges, including the risk of algorithmic bias, data privacy and security issues, issues of transparency (explainability) and accountability of algorithms, and capacity and infrastructure gaps. A comprehensive AI regulatory and governance framework, infrastructure and capacity investment, and an ethical and responsible implementation approach are needed, while still ensuring the central role of humans in the oversight process.